2013
DOI: 10.1007/s12195-013-0299-2
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Lines a Cell Contacts and Cell Contractility Drive the Efficiency of Contact Guidance

Abstract: Cell migration is an important biological function that impacts many physiological and pathological processes. Often migration is directed along various densities of aligned fibers of collagen, a process called contact guidance. However, cells adhere to other components in the extracellular matrix, possibly affecting migrational behavior. Additionally, changes in intracellular contractility are well known to affect random migration, but its effect on contact guidance is less known. This study examines differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 53 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…In addition to gratings, μCP has been used as a contact guidance cue. The average directionality increases with increased line period [60, 61], spacing [15, 16] and adhesiveness [15, 16]. The directionality of MTLn3 cells in this study matches well with what we have seen previously [15].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to gratings, μCP has been used as a contact guidance cue. The average directionality increases with increased line period [60, 61], spacing [15, 16] and adhesiveness [15, 16]. The directionality of MTLn3 cells in this study matches well with what we have seen previously [15].…”
Section: Discussionsupporting
confidence: 88%
“…The average directionality increases with increased line period [60, 61], spacing [15, 16] and adhesiveness [15, 16]. The directionality of MTLn3 cells in this study matches well with what we have seen previously [15]. When comparing gratings to μCP lines of ECM, others have shown that gratings are less potent than lines at dimensions that approximately match ours [62], whereas larger dimensions show that gratings are more potent [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 1/2-22 mm square coverslips (Corning Inc., Corning, New York, USA) were sonicated 30 minutes in the following solutions to make squeaky clean coverslips: hot tap water with Versa Clean detergent (Fisher Scientific, Hampton, New Hampshire, USA), hot tap water, distilled water, double distilled water, 1 mM EDTA solution (Fisher Scientific, Hampton, New Hampshire, USA), 70% ethanol in water and 100% ethanol. An adaptation of a protocol to functionalize coverslips with glutaraldehyde was used [40,41]. Cleaned coverslips were soaked in a 3:1 sulfuric acid (Fisher Scientific, Hampton, New Hampshire, USA):30% hydrogen peroxide (Fisher Scientific, Hampton, New Hampshire, USA) solution for one hour, washed with double distilled water and placed in 10 mL of 1% aminopropyltriethylsilane (APTES) (Fisher Scientific, Hampton, New Hampshire, USA) in 10 mM acetic acid for two hours.…”
Section: Collagen Substrate Treatmentmentioning
confidence: 99%